Structural health building response induced by earthquakes: Material softening and recovery. Issue 9 (27th July 2020) - Astorga, Ariana; Guéguen, Philippe
Abstract: Under proper loading conditions, micro‐to‐nanoscale heterogeneities (ie, the bond system ) that are commonly found within the materials of a system can coalesce until causing macroscopic alterations of the system properties. The bond system is responsible for atypical and invariant‐scale nonlinear elastic processes in granular media, from laboratory‐tested materials (mm) to the Earth's crust (km). The unusual observed behavior involves slow recovery, or relaxation, of the elastic properties after dynamic loading. Several models have been designed to explain non‐linear elasticity, although their physics is still partially unknown. Here, we show that recovery processes are also observed at intermediary scales (m) in civil engineering structures, and that they might be related to structural health due to the healing of cracks. For Japanese buildings subjected to earthquakes, we observe rapid co‐seismic reductions of their resonance frequency, followed by fascinating recoveries over different time scales. For the first time, slow recovery is presented in buildings over short times (ie, seconds) for a single earthquake; over intermediate times (ie, months) for a sequence of aftershocks; and over long times (ie, years) for a series of earthquakes. This study focuses on the analysis of long‐term recovery and recovery during aftershocks, in order to detect permanent damage. By comparing two buildings with different damage levels after the 2011 Tohoku earthquake, we show how relaxation models can characterize the level of cracking caused by damaging events. Our results demonstrate that nonlinear elasticity, combined with existing monitoring techniques, can be a powerful approach for damage detection and damage characterization. Abstract : This article presents the time scales of frequency recovery in buildings subjected to earthquakes, adapting theoretical models to real earthquake data in order to infer damage, providing insights of the internal structural state